Trends in Bloodstream Infection in Tertiary Care Hospital: A Retrospective Cross-sectional Study - Ranjit, Srijana; Katuwal, Nishan (Journal of Nepalgunj Medical College, 2021)
Introduction: Bloodstream Infection is one of the leading causes of mortality and morbidity among various groups of patients in a developing country like Nepal. Identification of the bacteria and their susceptibility to commonly used antibiotics is very essential for the treatment of the patients. Aims: This study aims to analyze current trends in bloodstream infection by accessing their bacteriological profile and antibiotic susceptibility. Methods: This is a hospital-based retrospective analysis of blood cultures of patients suspected with bloodstream infection. We conducted a three years (January 2018 to January 2021) retrospective analysis of blood culture reports from patients suspected with bloodstream infection. Data of the laboratory reports were used to determine bloodstream infection, blood culture contamination, pathogen profile and antimicrobial resistance patterns. Results: Out of 12811 blood samples that were sent to microbiology laboratory for culture, 438 were positive cultures. The most common etiological agent causing Bloodstream Infection was found to be Salmonella Typhi with129 isolates (29.6%) followed by Escherichia coli (21.9%). There was a significant rise in resistance to most of the frequently used antibiotics. Conclusion: Salmonella Typhi is the most frequent bacteria to be isolated in Bloodstream Infection. Resistance towards different etiological agents of Bloodstream Infection is alarmingly increasing every year. Resistance to frequently prescribed drugs should be of concern to the clinicians prescribing the drugs.